ABOUT 21st RUN OF WET: PG 1336-018 - Dorokhova, T. N.; Dorokhov, N. I.; Solheim, J. -E.; Gonzalez Perez, J. M. (Одеські астрономічні публікації, 2017)
We brie communicate about 21st run of the Whole Earth Telescope (WET) in April 2001, where the eclipsing short period binary sdB system PG 1336-018 was the primary target.